The The Role of Digital Marketing and Access to Financing in Improving the Competence of Women MSME Actors in Bekasi Regency - Purnamasari, Pupung; Hairiah, Fiqih Maria Rabiatul; Yahya, Adibah; Rahmiati, Filda (Syntax Corporation, 2025)
This research aims to examine the influence of digital marketing, financial inclusion with the mediation of financial literacy, towards the performance of women-led Micro Small and medium Expertise (MSMEs) locating in Bekasi Regency, Indonesia. The data were obtained from questionnaires distributed from a sample of 300 women-led MSME actors located specifically in Bekasi Regency. Quantitative approach was applied to test each variable while utilizing Partial Least Square Structural Equation Modeling (PLS-SEM) for statistical analysis. This study found that digital marketing, financial inclusion, and financial literacy has a positive and significant influence on MSEMs competency. Added, financial inclusion is directly related to financial literacy, which therefore influence the indirect relationship between financial inclusion and business competence.Female entrepreneurs who led micro, small enterprises can benefit from integrated digital literacy program learning programs that foster task-related abilities in the optimal use of digital technology. Financial service providers must continue educating the public on the range of financial service available. Accelerated proactive measures are required to ensure that entrepreneurs have a sufficient level of digital marketing and financial inclusion. Additionally, both official and informal education can incorporate entrepreneurial financing to guarantee that all society have equal access, regardless of their financial situation.The novelty of this research is specifically investigating the impact of digital marketing and access to finance, particularly financial inclusion and financial literacy, on improving the capabilities of women-led MSMEs.